Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.